Challenges in managing high-rise office building: a case study of a government building, Ipoh City Council in Perak / Fazilatul Fatihah Mohd Gazali - Mohd Gazali, Fazilatul Fatihah (Universiti Teknologi MARA (UiTM), 2025)
The research focuses on the challenges in managing high-rise office buildings, a case study of government buildings at Ipoh City Council, Perak where a lack of standard operating procedures for maintenance has led to disputes over costs and inadequate management practices. The study aims to identify maintenance practices, common challenges with objectives to assess and rank these challenges. The significance of this research lies in promoting sustainability, enhancing user experience, and contributing to academic knowledge in urban and facility management.